Cand. theol. Haraldur Nielssons oversættelsesvirksomhed og de første tilløb til »bibelkritik« på Island - Nielsen, Jens Hvidtfeldt; Jonsson, Gunnlaugur A. (Kirkehistoriske Samlinger, 1995)
No other Icelander has translated as much of the Bible as Haraldur Nielsson (1868-1928), who personally translated the greater part of the Old Testament, although his work was reviewed by a translation committee. This article discusses Haraldur’s translation of the Old Testament, carried out between 1897 and 1907, and the connections between his translation work and the introduction of the historical-critical method in Iceland. The method of historical criticism was hotly disputed in Iceland at the time of its introduction, and reactions to Haraldur’s translation were heavily influenced by the position which readers and critics took toward the new critical method. This article describes the background of these disputes. Attention is, for example, drawn to the fact that historical criticism had not yet gained much of a following at the University of Copenhagen in the years around 1890 when the Icelandic »Tum-of-the-Century-Theologians« were studying there. It was through visits to German universities that Icelandic theologians became acquainted with the new critical method. Haraldur Nielsson was one of the pioneers of historical criticism in Iceland, and his opponents found numerous traces of this new method in his translation. They called the translation the »heathen Bible«; but others could barely find words sufficient to express their delight and admiration, and maintained that few other nations possessed a Bible translation as successful as Haraldur’s. In those years, Haraldur was becoming one of the most zealous proponents of spiritualism in Iceland, and many people claimed to find reflections of this in his translation. The use of the name Jahve in the translation, instead of the traditionally-used expression, Drottinn (the Lord), also attracted criticism. It was not these matters but others, however, which formed the principal basis of a complaint lodged with the British and Foreign Bible Society, the financial sponsor of the translation. Haraldur had to go abroad to answer this comnplaint. A compromise was reached in the which he agreed to make changes in two places: Isaiah 1:18 and 7:14. The final part of this article attempts to answer the question why a new Bible translation is needed. It is pointed out that in Iceland the simple argument that the language has changed has less application than in most other countries. Linguistic conservatism has long been accounted a great virtue in Iceland. The main reason presented in favor of a new translation is rather that approaches to translation have changed. The announced objective of those who carried out the 1908/12 translation was to translate »word for word«. That approach is here rejected, and the ideas of E.A. Nida suggested as a better alternative.